Pyroptosis and Its Regulation in Diabetic Cardiomyopathy - Lu, Yafang; Lu, Yaqiong; Meng, Jun; Wang, Zuo (Frontiers in Physiology, 2022)
Diabetic cardiomyopathy (DbCM) is a prevalent disease, characterized by contractile dysfunction and left ventricular hypertrophy. Patients with DbCM have high morbidity and mortality worldwide. Recent studies have identified that pyroptosis, a kind of cell death, could be induced by hyperglycemia involved in the formation of DbCM. This review summarizes the regulatory mechanisms of pyroptosis in DbCM, including NOD-like receptor3, AIM2 inflammasome, long non-coding RNAs, microRNAs, circular RNA, autophagy, and some drugs.